Corporate Digital Responsibility: Review - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Increasing the prevalence of digital technologies and related data, and that ethical concerns arise as a result. Looking at four main stakeholders and propose a novel concept in the field of corporate digital responsibility (CDR). Under this paper CDR is defines as the set of shared values and standards which guide the operations of an organization in relation to four main processes related to digital technology and data. Such methods are the creation of technology and data collection, activity and decision-making, review and effect evaluation, and technology and data refining. Discussion is expanded our by highlighting how to manage behavior that is compliant with CDR based on a perspective of organizational culture. Our conceptualization opens possibilities for future research, particularly with regard to specific contexts and implications. Managingly, we shed first light on how the shared values and standards of an organization regarding CDR can be translated into user-friendly guidelines. It offers foundations for future discussions on planning, deployment and progress of CDRs.